2019
DOI: 10.1093/comjnl/bxz064
|View full text |Cite
|
Sign up to set email alerts
|

DeepDetect: Detection of Distributed Denial of Service Attacks Using Deep Learning

Abstract: At the advent of advanced wireless technology and contemporary computing paradigms, Distributed Denial of Service (DDoS) attacks on Web-based services have not only increased exponentially in number, but also in the degree of sophistication; hence the need for detecting these attacks within the ocean of communication packets is extremely important. DDoS attacks were initially projected toward the network and transport layers. Over the years, attackers have shifted their offensive strategies toward the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Deep learning algorithms have also been used in SDN-based architectures to solve the problem of intrusion detection [16][17][18]. Other deep learning algorithms [19,20] have been applied in non-SDN architectures to detect DDoS and intrusion detection.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning algorithms have also been used in SDN-based architectures to solve the problem of intrusion detection [16][17][18]. Other deep learning algorithms [19,20] have been applied in non-SDN architectures to detect DDoS and intrusion detection.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that their system outperformed conventional machine learning models. Furthermore, Asad's team [26] proposed a deep neural network-based system that Fig. 2 DDoS attacks utilising different attack types uses feed-forward back-propagation.…”
Section: Related Workmentioning
confidence: 99%
“…The complexity of the model increasing the level of difficulty for duplicating the model Asad [26] Simplicity of the model making it easy to understand and duplicate Potential performance reduction on data sets with different attacks exhibiting different traffic patterns Salama [27] Applying RBM to select features for a SVM Requirement an additional machine learning model for classification are provided in the 'Target Detector' section. Furthermore, to reduce the variance of the system, the IAM applies an ensemble technique by employing RAAs as base learners and utilising a majority voting scheme to attain the final classification.…”
Section: System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods such as the auto-encoder neural network [27], Long and Short Time Memory network (LSTM) [28] and the CNN [29] are also used to detect the anomaly through encoding the traffic. Furthermore, some researches have been carried out based on the environmental feature of multi-flows [30], which applied the DNN to learn the characteristics of the network flow.…”
Section: Related Workmentioning
confidence: 99%